Identifying an optimal dihydroartemisinin-piperaquine dosing regimen for malaria prevention in young Ugandan children - Erika Wallender (Nature Portfolio, 2021)
Intermittent preventive treatment with dihydroartemisinin-piperaquine (DP) is protective in children against malaria. Here, the authors analyze plasma drug concentration, malaria incidence, and drug resistance markers from a clinical trial in Uganda and determine the optimal DP dosing regimen.